Lutra lutra - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2009)
34. Eurasian Otter Lutra lutra French: Loutre d'Europe / German: Eurasischer Fischotter / Spanish: Nutria paleartica Other common names: European Otter Taxonomy. Mustela lutra Linnaeus, 1758, Sweden. The Japanese Otter (L. nippon) is considered by some authors to be a valid species, based on recent morphological and molecular analyses. However, further research is needed to determine its taxonomic status; it is here considered a subspecies of L. lutra. Up to twenty-eight subspecies have been proposed, but a taxonomic revision is needed. Distribution. Wide distribution in the Palearctic: from Europe to Russian Far East, North and South Korea, and Japan; also N Africa, Middle East, C Asia, Sub-Himalayan zone, S India, Sri Lanka, C, E & S China, Taiwan, Indochina, and Sumatra. Descriptive notes. Head-body 50-82 cm, tail 33-50 cm; weight 5-14 kg, adult males are typically 50% larger than females. The Eurasian Otter has a long body and a conical tail. The short, dense pelage is brown to almost black throughout, with slightly paler undersides. The legs are short; the feet are fully webbed and have well-developed claws. There are two to three pairs of mammae. The cranium is large and flat. Dental formula: 13/3, C1/1,P 4/3, M 1/2 = 36. Habitat. Eurasian Otters are found along lakes, ponds, rivers, and streams, and in marshes, swamps, and coastal and estuarine wetlands, from sea level up to 4120 m. They avoid areas of deep water. Food and Feeding. The diet is mainly fish, frogs, and aquatic invertebrates (including crustaceans and crabs). Birds and small mammals (such as rodents and lagomorphs) may be consumed on occasion. In general, the mean proportion offish declines from 94% on seashores, to 71% on lakes and fish ponds, to 64% on rivers and streams. On inland waters, the abundance of crayfish is an essential food item. In Northern Ireland, over 50% of spraints were composed of sticklebacks (Gasterosteus aculeatus), salmonids and cyprinids, with Sticklebacks constituting the most frequently occurring prey ...